Factores psicosociales y la dependencia al alcohol de los internos del Centro de Rehabilitación de Adicciones 24 Horas del cantón San José de Chimbo, periódo noviembre 2023 – mayo 2024 - Barragán Verdezoto, Eduardo Joselo (2024)
The interaction between psychological and social factors creates a complex environment that impacts the lives of those who suffer from alcohol dependence. These components include, among others, stress, anxiety, depression, interpersonal relationships, family environment, social pressures, and traumatic experiences. The present curriculum integration work addresses the issue of alcohol dependence, exploring the psychosocial factors influencing the residents of the 24-Hour Addiction Rehabilitation Center in the San José de Chimbo Canton. It focuses on understanding the complexity of this addiction. This research is descriptive in nature, with a quantitative approach. It is worth mentioning that it is feasible due to the authorization, accessibility, and collaboration of the residents and representatives of the institution. It aims to address ethical considerations and confidentiality, utilizing updated bibliography and relevant research references. The results obtained indicate that daily alcohol consumption always negatively affects daily life and responsibilities, impacting 60% of the surveyed population. Additionally, 40% mention that this substance almost always affects their lives.